Risk factors for prosthetic joint infections following total hip arthro- plasty based on 33,337 hips in the Finnish Arthroplasty Register from 2014 to 2018 - Mäkelä, Keijo T; Panula, Valtteri J; Alakylä, Kasperi J; Venäläinen, Mikko S; Haapakoski, Jaason J; Eskelinen, Antti P; Manninen, Mikko J; Kettunen, Jukka S; Puhto, Ari-Pekka; Vasara, Anna I; Elo, Laura L (Acta Orthopaedica, 2021)
Background and purpose — Periprosthetic joint infection (PJI) is a devastating complication and more informa- tion on risk factors for PJI is required to find measures to prevent infections. Therefore, we assessed risk factors for PJI after primary total hip arthroplasty (THA) in a large patient cohort. Patients and methods — We analyzed 33,337 primary THAs performed between May 2014 and January 2018 based on the Finnish Arthroplasty Register (FAR). Cox proportional hazards regression was used to estimate hazard ratios with 95% confidence intervals (CI) for first PJI revision operation using 25 potential patient- and surgical- related risk factors as covariates. Results — 350 primary THAs were revised for the first time due to PJI during the study period. The hazard ratios for PJI revision in multivariable analysis were 2.0 (CI 1.3– 3.2) for ASA class II and 3.2 (2.0–5.1) for ASA class III–IV compared with ASA class I, 1.4 (1.1–1.7) for bleeding > 500 mL compared with < 500 mL, 0.4 (0.2–0.7) for ceramic-on- ceramic bearing couple compared with metal-on-polyeth- ylene and for the first 3 postoperative weeks, 3.0 (1.6–5.6) for operation time of > 120 minutes compared with 45–59 minutes, and 2.6 (1.4–4.9) for simultaneous bilateral operation. In the univariable analysis, hazard ratios for PJI revi- sion were 2.3 (1.7–3.3) for BMI of 31–35 and 5.0 (3.5–7.1) for BMI of > 35 compared with patients with BMI of 21–25. Interpretation — We found several modifiable risk factors associated with increased PJI revision risk after THA to which special attention should be paid preoperatively. In particular, high BMI may be an even more prominent risk factor for PJI than previously assessed.